Validation of the Spanish Version of the Psychosocial Assessment Tool (PAT) in Pediatric Cancer. (2nd July 2018) - Kazak, Anne E; Hwang, Wei-Ting; Chen, Fang Fang; Askins, Martha A; Carlson, Olivia; Argueta-Ortiz, Francisco; Vega, Gabriela; Barakat, Lamia P
Abstract: Objective: Family psychosocial risk screening is an important initial step in delivering evidence-based care and in addressing health disparities. There is currently no validated measure of family psychosocial risk in Spanish. The Psychosocial Assessment Tool (PAT) is a brief parent report screener based on the trilevel Pediatric Preventative Psychosocial Risk Model (PPPHM; Universal, Targeted, and Clinical). The current article validates a Spanish version of the PAT (Version 3.0) in pediatric oncology. Method: Spanish-speaking Hispanic primary caregivers of 79 children newly diagnosed with cancer participated in this 4-institution multisite investigation, completing Spanish versions of the PAT and validation measures using REDCap. Results: Over 60% of the sample had a high school or lower level of education and they primarily identified as Hispanic in terms of acculturation. Internal consistency for the total score (KR20 = 0.76) and the Social Support, Child Problems, Sibling Problems, and Family Problems subscales was strong (KR20 = 0.69–0.79). Stress Reactions, Family Structure, and Family Beliefs subscales were lower (KR20 = 0.43–0.55). Moderate to strong correlations with the criteria measures provided validation for the total and subscale scores. Nearly two-thirds of the sample scored in the Targeted or Clinical range of the PPPHM. The PAT was successful in identifying clinical cases. Conclusions: The Spanish version of the PAT can be used with families of children newly diagnosed with cancer. Elevated psychosocial risks were found and warrant particular attention in providing psychosocial care attentive to the needs of Spanish-speaking families.